2015
DOI: 10.3109/09638237.2015.1019050
|View full text |Cite
|
Sign up to set email alerts
|

Youth engagement with an emerging Irish mental health early intervention programme (Jigsaw): participant characteristics and implications for service delivery

Abstract: This study provides emerging evidence to support the need for an early intervention component within the system of mental health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 12 publications
2
37
0
Order By: Relevance
“…This programme was delivered in partnership with staff working in Jigsaw, an early intervention mental health service developed by Headstrong which provides mental health supports to 12-25 year olds. As of June 2014, ten communities with population catchment areas of 150,000-250,000 have opened Jigsaw programmes and are providing a range of early intervention services for young people (O'Keeffe, O'Reilly, O'Brien, Buckley, & Illback, 2015;O'Reilly, Illback, Peiper, O'Keeffe, & Clayton, 2015).…”
Section: Description Of Youth Mental Health Peer Education Training Pmentioning
confidence: 99%
“…This programme was delivered in partnership with staff working in Jigsaw, an early intervention mental health service developed by Headstrong which provides mental health supports to 12-25 year olds. As of June 2014, ten communities with population catchment areas of 150,000-250,000 have opened Jigsaw programmes and are providing a range of early intervention services for young people (O'Keeffe, O'Reilly, O'Brien, Buckley, & Illback, 2015;O'Reilly, Illback, Peiper, O'Keeffe, & Clayton, 2015).…”
Section: Description Of Youth Mental Health Peer Education Training Pmentioning
confidence: 99%
“…The My World Survey evaluated the positive and negative factors associated with mental health in a sample of 12-25 year old young people. The survey reported that 51% of young Irish adults report a lifetime history of suicidal ideation and 7% a lifetime suicide attempt, with a substantial proportion reporting clinically significant levels of anxiety (29%), depression (28%) and either problem alcohol use or abuse (61%) (Dooley & Fizgerald, 2012;Martin, Carr, Burke, Carroll, & Byne, 2006 & Clayton, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Jigsaw is a free and confidential service and is designed to promote systems of care that are accessible, youth-friendly and engaging for young people with mental health needs with the ambition that young people are connected to their community and have the resilience to face challenges to their mental health (www.jigsaw.ie/what-we-do). Young people are referred to Jigsaw from various sources including parents, self-referral, GPs and the MHSs (O'Reilly et al 2015). Jigsaw predominantly provides brief intervention support (typically 1-6 sessions) to young people aged 12-25 years with emerging mental health difficulties.…”
Section: Introductionmentioning
confidence: 99%